Early Years Physics Teaching of Abstract Phenomena in Preschool—Supported by Children’s Production of Tablet Videos - Andreas Redfors; Marie Fridberg; Agneta Jonsson; Susanne Thulin (Education Sciences, 2022)
In 2011, a renewed national curriculum for preschools in Sweden introduced explicit pedagogical tasks concerning chemistry and physics. This article is about the analysis of physics teaching supported by video productions with tablets, part of a three-year professional development programme on collaborative inquiry teaching of chemistry and physics in Swedish preschools. The temporal case studies reported here were focused on children’s and teachers’ communication during extended teaching sequences with three- to six-year-old children in two Swedish preschools. Eleven children and two teachers participated in this study. The children worked in small groups with one teacher. Results indicate that children’s video productions by tablets contributed to children’s learning, with differences indicated for children’s experiences of objects of learning in physics at different levels of abstraction. Consequences of the results for future teaching of early years physics are discussed.